1985
DOI: 10.1172/jci112091
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of hydrocortisone on eosinophil and neutrophil proliferation.

Abstract: Glucocorticosteroid therapy results in an increase in the number of circulating neutrophils and a decrease in the number of eosinophils. Utilizing the double layer soft agar technique, we examined the effect of physiologic to pharmacologic concentrations of hydrocortisone on the proliferation of human neutrophil progenitors and eosinophil progenitors from peripheral blood and bone marrow. When peripheral blood cultures were studied, eosinophil proliferation was inhibited in a dose-responsive fashion with 10"-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
2
1

Year Published

1987
1987
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 19 publications
1
25
2
1
Order By: Relevance
“…Both factors are known to increase WBC counts by increasing neutrophil influx from marrow storage and decreasing efflux from the blood stream (32,33). In addition, cortisol and insulin may increase the WBC count by stimulating leptin secretion from adipocytes (34).…”
Section: Discussionmentioning
confidence: 99%
“…Both factors are known to increase WBC counts by increasing neutrophil influx from marrow storage and decreasing efflux from the blood stream (32,33). In addition, cortisol and insulin may increase the WBC count by stimulating leptin secretion from adipocytes (34).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the biosynthesis of PAF-acether is also associated with the release of the arachidonic acid by PLA2 [26], and this might also account for the effective ness of the dexamethasone. However, the interference of corticosteroids with the production of citokines associated with eosinophil activation [27] and/or eosinopoiesis [28] cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the effect was said to be dose-dependent in the HC concentration range from 10"9to 10'5 M (although no data were presented), despite the fact that the lowest level would be within the range of HC concentrations in the fetal bovine serum constituent of the culture system [1], Again, using peripheral blood mononuclear cells, Bjornson and Harvey [4] found no stimulation of GM colony growth by HC in agar, although the propor tion of eosinophil colonies was reduced, and in long term liquid cultures of human BM containing HC at 10~6 M, no eosinophil colony-forming cells were generated [5]. Even more recently, these authors [6] have reported that eosinophil colony formation, in cultures of peripheral blood and unseparated BM cells, was inhibited by HC at 10-7 to 10'5 M, while the number of neutrophil colonies was increased. How ever, in the latter report the culture interval is not given; inhibition of clonogenesis was observed with progesterone at 10"7 M (a physiological concentration [ 12]; and there was no competition between the effects of progesterone and HC [1], although it is not re corded whether the concentrations of these hormones in such experiments were equimolar.…”
Section: Discussionmentioning
confidence: 99%